2004
DOI: 10.1161/01.cir.0000148980.87579.5e
|View full text |Cite
|
Sign up to set email alerts
|

CDC/AHA Workshop on Markers of Inflammation and Cardiovascular Disease

Abstract: 1. Of the inflammatory markers identified, C-reactive protein (CRP) has the analyte and assay characteristics that are the most conducive for use in practice. 2. To obtain a CRP concentration in metabolically stable patients, 2 measurements, fasting or nonfasting, should be made (optimally 2 weeks apart) and the results averaged. If the CRP level is Ͼ10 mg/L, then the test should be repeated and the patient examined for sources of infection or inflammation. 3. CRP results should be expressed only as milligrams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(94 citation statements)
references
References 37 publications
4
86
0
1
Order By: Relevance
“…First, we found that in the group with little changes in lifestyle (control group), elevated levels of CRP were associated with increased type 2 diabetes incidence. Elevated CRP is by far the best characterized immunological risk factor for incident type 2 diabetes because international standards for the assessment of CRP levels exist (26,27) and because this association could be confirmed in a range of independent studies (9 -12,14,15). Previous studies have shown that elevated CRP levels indicate increased risk of type 2 diabetes in population-based cohorts (8 -10).…”
Section: Resultsmentioning
confidence: 99%
“…First, we found that in the group with little changes in lifestyle (control group), elevated levels of CRP were associated with increased type 2 diabetes incidence. Elevated CRP is by far the best characterized immunological risk factor for incident type 2 diabetes because international standards for the assessment of CRP levels exist (26,27) and because this association could be confirmed in a range of independent studies (9 -12,14,15). Previous studies have shown that elevated CRP levels indicate increased risk of type 2 diabetes in population-based cohorts (8 -10).…”
Section: Resultsmentioning
confidence: 99%
“…Values lower than the detection limit [0.154 mg L −1 for CRP (multiplied by 9524 to express the value in mmol L −1 ) and 0.08 pg mL −1 for IL‐6] were assigned a value equal to half the detection limit. We excluded samples with CRP concentrations suggestive of acute inflammation and related bacterial infection (>10 mg L −1 ) 49 ( n = 242). To measure short‐term biological variation and laboratory error, a repeat sample was taken from 150 participants for CRP and 241 participants for IL‐6 at phase 3 [with a mean elapsed time between samples of 32 days (SD 10.5)].…”
Section: Methodsmentioning
confidence: 99%
“…Ceiling effects mainly affected CRP levels for which the upper value was set to 10 mg/L, but upper limits are not defined for IL-6. (Myers et al, 2004) Participants who reported recent colds or flu, or with high CRP levels, were excluded since a high value is considered to indicate acute inflammation and immune activation due to current illness potentially masking the relatively small elevations that may be associated with psychosocial factors or even chronic disease risk. Those acute, and typically large, responses are qualitatively different from the effects of chronic health conditions, such as the ones we adjusted for, and are short-term reactions not representative of the individual.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…At baseline and follow-up, we excluded those with high CRP values (>10mg/L) and those who reported a cold or 'flu' in the last two weeks since these conditions are typically related to short-term large responses not representative of the individual. (Myers et al, 2004) This left 5978 participants with CRP and 5907 with IL-6 data at baseline. Of these, 3339 (CRP) and 3298 (IL-6) also had measurements of cognitive symptoms at baseline and at follow-up.…”
Section: Design/setting and Participantsmentioning
confidence: 99%